2011
DOI: 10.2217/pgs.11.33
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the CYP3A4*1G Polymorphism and its Combination with CYP3A5 Genotypes on Tacrolimus Pharmacokinetics in Renal Transplant Patients

Abstract: The CYP3A4*1/*1G polymorphism was associated with the pharmacokinetics of tacrolimus, however, its contribution to dose-adjusted pharmacokinetics was approximately twofold less than that of the CYP3A5*1/*3 polymorphism. Although its effect on CYP3A4 activity is not clear, CYP3A4*1/*1G may be a candidate for a polymorphism affecting the interindividual variability in tacrolimus pharmacokinetics among CYP3A5 expressers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 28 publications
8
60
2
Order By: Relevance
“…19,[24][25][26] In the present study, CYP3A4*1G genotype showed a significant association with the C/D ratio of tacrolimus in living-donor liver transplant patients comparable with data reported in kidney transplantation. 9) We showed CYP3A4*1G genotype had no correlation with the mRNA expression level of CYP3A4 both in graft liver and native intestine. Consistent with the finding by Fukushima-Uesaka et al, 8) our results showed that the CYP3A4*1/*1 genotype was strongly linked with the CYP3A5*3/*3 genotype (93.6%).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…19,[24][25][26] In the present study, CYP3A4*1G genotype showed a significant association with the C/D ratio of tacrolimus in living-donor liver transplant patients comparable with data reported in kidney transplantation. 9) We showed CYP3A4*1G genotype had no correlation with the mRNA expression level of CYP3A4 both in graft liver and native intestine. Consistent with the finding by Fukushima-Uesaka et al, 8) our results showed that the CYP3A4*1/*1 genotype was strongly linked with the CYP3A5*3/*3 genotype (93.6%).…”
Section: Discussionmentioning
confidence: 64%
“…4,5) However, a newly identified SNP in the CYP3A4 gene, CYP3A4*1G affects the pharmacokinetics of some drugs. 7,9,21,22) Although some SNPs in the CYP3A4 gene such as CYP3A4*1B and CYP3A4*22 have been reported to affect the pharmacokinetics of tacrolimus, 17,23) the frequencies of CYP3A4*1B and CYP3A4*22 have not been observed in Chinese and Japanese patients. 19,[24][25][26] In the present study, CYP3A4*1G genotype showed a significant association with the C/D ratio of tacrolimus in living-donor liver transplant patients comparable with data reported in kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other study [45] was conducted in South China (Shanghai), where the majority of the population is Han Chinese. These conflicting results might be attributable to linkage disequilibrium (LD) between CYP3A4*1G and CYP3A5*3 in Asian populations [47][48][49] , including Han Chinese in South China [47] .…”
Section: Cyclosporine Amentioning
confidence: 99%
“…CYP3A4*1G is a CYP3A4 SNP with the highest occurrence in Chinese populations, but a definitive function has not been reported. A series of studies examined the relationship between the CYP3A4*1G polymorphism and drug metabolism but resulted in inconsistent findings [32][33][34] . In agreement with our observation, CYP3A4*1G was not associated with cyclosporine concentrations in 126 renal recipients [27] ; however, Qiu et al [22] and Hu et al [35] found that it was associated with a lower CsA concentration.…”
Section: Discussionmentioning
confidence: 99%